Peranan Pemerintah dalam Menghadapi Pandemi Covid-19 pada Bidang Pendidikan di Indonesia - Ratu Raisya Aghnia Azhara; Dede Sri Kartini (Universitas Medan Area, 2022)
The whole world was shocked by the Covid-19 pandemic. Broadly speaking, the Covid-19 virus has had several effects on education in Indonesia, which can be divided into two categories, both positive and negative. Talking about education, education is a field that can be categorized as important in people's lives, especially in developing Human Resources (HR) in Indonesia. With the existence of education, the next generation will be filled with individuals who are outstanding, intelligent, and useful for the homeland and nation. Therefore, with the spread of the Covid-19 virus, the government in Indonesia is expected to be able to provide an essential and beneficial role for the people in Indonesia. This study aims to determine the role of the government in dealing with the Covid-19 pandemic in the education sector. This research uses qualitative research, by conducting literature studies and documentation studies. This study found that the government's role in dealing with the Covid-19 pandemic in the education sector is in line with government functions: 1) Service functions: Provision of Quota Subsidies, Providing BOP and BOS, Teacher Sharing Platforms, Formation of Emergency Curriculum, Formation of Independent Curriculum, and SKB. 2) Empowerment Function: The government provides an Independent Learning program. 3) Development Function: the government builds hard infrastructure, either in the form of satellite, broadband, or tower so as to improve connectivity.